2011
DOI: 10.1016/j.chc.2011.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Behavioral Therapy for Adolescent Depression and Suicidality

Abstract: Synopsis CBT has emerged as a well-established treatment for depression in children and adolescents but treatment trials for adolescents with suicidality are few in number, and their efficacy to date is rather limited. Although a definitive treatment for adolescent suicide attempters has yet to be established, the limited literature suggests that suicidal thoughts and behavior should be directly addressed for optimal treatment outcome. This chapter reviews the rationale underlying the use of CBT for the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 43 publications
7
73
0
3
Order By: Relevance
“…80,81 CBT included up to 20 sessions plus up to four parent sessions over 30 weeks. CBT therapists were routine CAMHS clinicians and were either clinical psychologists or other clinicians who had received post-qualification training in CBT.…”
Section: Cognitive-behavioural Therapymentioning
confidence: 99%
“…80,81 CBT included up to 20 sessions plus up to four parent sessions over 30 weeks. CBT therapists were routine CAMHS clinicians and were either clinical psychologists or other clinicians who had received post-qualification training in CBT.…”
Section: Cognitive-behavioural Therapymentioning
confidence: 99%
“…Possibly, future research may benefit from a more thorough examination of more subtle commonalities between suicide only interventions and those that target depression Overall, the findings of this review add a number of new dimensions to previous similar reviews. This review provides partial support for the review by Spirito et al (2011) which found CBT depressive interventions have equivalent efficacy for suicidality when compared to other treatments. The results of our review differ to the previous review on psychological therapy for depression in adolescents by Weisz et al (2006), which found psychological interventions have only marginal effects on suicidality.…”
Section: Discussionmentioning
confidence: 83%
“…The Weisz review noted considerable heterogeneity in the type of control group employed by the different studies, including medication placebos, supportive therapy and a waiting list control. Finally, a more recent literature review of seven studies focused specifically on CBT for the treatment of adolescent depression and its effect on suicidality (Spirito et al, 2011) and concluded that most CBT intervention studies provide comparable reductions in suicidality to family therapy, supportive therapy and pharmacotherapy, but show the most promise for also reducing major depressive disorder (MDD) diagnoses and depressive symptoms. This however conflicted with the Weisz et al (2006) meta-analysis which did not find any evidence that cognitive treatments are more effective than noncognitive approaches.…”
Section: Suicidality and Adolescent Depressionmentioning
confidence: 99%
“…Bu alandaki çalışmaların çoğu bilişsel davranışçı terapinin özkıyım düşüncesini azalttığını bildirmektedir. [33,59] Ancak, klinik belirtilerle başvuran çocuk ve ergen grubun bilişlerine yönelik yeterli sayıda veri bulunmamasının bu alandaki terapinin uygulanması ve etkinliğinin ortaya konması üzerinde etkisi olabileceği de belirtilmiştir. [60] Sonuç Özkıyım, ergen ruh sağlığı açısından oldukça önemli bir konudur.…”
Section: Tedavi öNerileriunclassified